Perspectivas da governança fundiária: Projeto regulariza Amazônia cooperação bilateral Brasil-União Europeia - Alyson Fernando Alves Ribeiro (Confins)
This article is a result of postdoctoral research. It seeks to analyze the results of the Regulariza Amazônia Project. An Incra - European Union partnership with the aim of improving and accelerating the process of allocation and land tenure regularization of public lands under the Terra Legal Program in four states: Pará, Mato Grosso, Amazonas and Amapá. From this bilateral cooperation between Incra and the European Union with a strategic focus from the perspective of land governance, the various developments for the agrarian space of the Amazon deserve investigation, being fundamental for the epistemic construction of the reflection on the (re)production of the agrarian space of the Amazon and its (re)significations in time-space. The project promoted actions regarding the operational and technical modernization of the land collection in the Amazon. Conducted consultancy and promoted innovations in the management of public lands carried out by Incra: Technical support to the Land Management System; Updating and adaptation of the Territorial Intelligence Panel (PIT); Structuring and maintenance of the geospatial database; Methodological improvement of the technical chamber for the allocation of federal public lands. Distorting its purpose, the methodological technical support in the modernization of INCRA's land management, becomes the institutional contradictions of the autarchy, in a gear for the global land market (land global).